Impact of Entrepreneurship on Economic Growth of Farmers in Manipur (Indian Journal of Extension Education, 2016)
The present study was carried out on 400 households, belonging to 4 blocks of Senapati district of Manipur during 2013- 15. Senapati district was selected keeping in view of major concentration of tribals with highest pig population in the state of Manipur. A sample of farmers comprising of 100 respondents from each block was selected for the present study. Locations had significant (P<0.01) influence on annual family income of farmers obtained from various sources viz. piggery, total livestock and total income from all sources. However, its effect had nonsignificant influence on annual family income came from other livestock except piggery and other sources (Agriculture, Horticulture etc.) Socio-personal variables such as age, family size and education were not significantly correlated to the economic growth of farmers. However, herd size of pigs had positively and significantly correlated with annual income of family from there different sources.